Studies on Pollen Viability of Male Parent in Tomato Hybrid Seed Production - R.B. JOLLI; B.S. VYAKARANAHAL; M. SHEKARAGOUDA; P.R. DHARMATTI; A.A. PATIL (Seed Research, 2026)
In order to know the pollen viability for hybrid seed production in tomato a study on pollen viability was undertaken at Agricultural Research Station, Hanumanamatti of Haveri District in Karnataka during 2002 and 2003. In this study the pollens where stored for one day, two days and three days under ambient and refrigerated condition along with fresh pollen were used for pollination in the production of hybrid seed of DTH-1. The results revealed that there was a significant variation in pollen viability due to age of the pollen and storage conditions. Pollen stored under refrigerated condition for two days found significantly superior with respect to fruit set, fruit yield, seed yield and quality as compared to ambient stored and use of fresh pollen for pollination.